The remaining barriers to normalcy in CF: Advances in assessment of CF lung disease. (12th January 2021) - Muston, Heather N.; Perrem, Lucy; Davis, Michael D.; Ratjen, Felix; Ren, Clement L.
Abstract: Despite early diagnosis of cystic fibrosis (CF) through newborn screening, a substantial proportion of infants and young children with CF still demonstrate physiologic and structural evidence of lung disease progression, such as obstructive airway disease and bronchiectasis. The growing availability of highly effective CF transmembrane conductance regulatory modulator therapy to the vast majority of people with CF has led to the potential to alter the natural history of CF lung disease, but to assess the full impact of these therapies on CF lung disease and to help guide treatment, sensitive measures of early and mild disease are needed. Chest imaging using computed tomography or magnetic resonance imaging is one approach, but technologic barriers and/or concern about exposure to ionizing radiation may limit its use. However, advances in physiologic measurement techniques and exhaled breath analysis offer another option for assessment of CF lung disease